2020
DOI: 10.1101/2020.06.29.178970
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural signatures of vigilance decrements predict behavioural errors before they occur

Abstract: AbstractThere are now many environments in which humans need to monitor moving displays and only rarely act, such as train control and driving autonomous vehicles; lapses of attention in these circumstances can have tragic consequences. Problematically, we know that it is difficult to sustain attention under these monitoring or vigilance conditions and performance drops: when target events are rare, we tend to miss them, or are slower to respond. This ‘rare target’ effect becom… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…The RSA-based connectivity method used in this study further develops a recent shift towards multivariate brain connectivity methods (Anzellotti and Coutanche, 2018;Basti et al, 2020;Keitzmann et al, 2019;Goddard et al, 2016;Clarke et al, 2018;Karimi-Rouzbahani, 2018;Karimi-Rouzbahani et al, 2019;Karimi-Rouzbahani et al, 2020), and introduces several advantages over previous methods of connectivity analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The RSA-based connectivity method used in this study further develops a recent shift towards multivariate brain connectivity methods (Anzellotti and Coutanche, 2018;Basti et al, 2020;Keitzmann et al, 2019;Goddard et al, 2016;Clarke et al, 2018;Karimi-Rouzbahani, 2018;Karimi-Rouzbahani et al, 2019;Karimi-Rouzbahani et al, 2020), and introduces several advantages over previous methods of connectivity analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The RSA-based connectivity method used in this study follows a recent shift towards informational brain connectivity methods (Anzellotti and Coutanche, 2018; Basti et al, 2020; Keitzmann et al, 2019; Goddard et al, 2016; Clarke et al, 2018; Karimi-Rouzbahani, 2018; Karimi-Rouzbahani et al, 2019; Karimi-Rouzbahani et al, 2020a), and introduces a few distinct features compared to previous methods of connectivity analyses. Specifically, traditional connectivity methods examine inter-area interactions through indirect measures such as gamma-band synchronization (Gregoriou et al, 2009), shifting power (Bar et al, 2006) or causality in the activity patterns (Summerfield et al, 2006; Fan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karimi-Rouzbahani et al, 2017a have shown discrepancy across studies/datasets. This suggest that their results might have been driven by category-irrelevant task features such as attentional load or task demands, which can modulate the neural activity to a greater level than that evoked by the stimulus (Karimi-Rouzbahani et al, 2019;Karimi-Rouzbahani et al, 2020b). Therefore, a wider set of features and datasets should be evaluated to reach more generalizable conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Third, temporal variability of brain activity should not be overlooked, as this is generally the case in multivariate decoding (Karimi-Rouzbahani et al, 2019), as the temporal codes can contain additional information. Forth, as the brain seem to process the face and object information using a common set of neural infrastructures (Dobs et al, 2019), but constructs face representations which outperform object representations (Fig. 2B), the current deep networks of object recognition, may benefit to follow the brain and move towards a unified platform for face and object recognition.…”
Section: Discussionmentioning
confidence: 99%